2011
DOI: 10.1088/0004-637x/731/1/6
|View full text |Cite
|
Sign up to set email alerts
|

The Nature of the Warm/Hot Intergalactic Medium. I. Numerical Methods, Convergence, and O Vi Absorption

Abstract: We perform a series of cosmological simulations using Enzo, an Eulerian adaptive-mesh refinement, N-body + hydrodynamical code, applied to study the warm/hot intergalactic medium. The WHIM may be an important component of the baryons missing observationally at low redshift. We investigate the dependence of the global star formation rate and mass fraction in various baryonic phases on spatial resolution and methods of incorporating stellar feedback. Although both resolution and feedback significantly affect the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

26
244
5

Year Published

2016
2016
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 145 publications
(275 citation statements)
references
References 74 publications
(133 reference statements)
26
244
5
Order By: Relevance
“…In conclusion, the AGN model from OWLS and the simulations from Smith et al (2011) predict absorber properties that are compatible with our observations and in line with the idea, that the majority of the Si iii absorbers at z ≤ 0.1 arise in the extended halos of low-redshift galaxies. For the future, we are planning to further explore the relation between intermediate-ion absorbers and galaxies at low z using higher-resolution simulations from the EAGLE (Evolution and Assembly of GaLaxies and their Environments) project (Schaye et al 2015).…”
Section: Comparison With Hydrodynamical Simulationssupporting
confidence: 89%
See 1 more Smart Citation
“…In conclusion, the AGN model from OWLS and the simulations from Smith et al (2011) predict absorber properties that are compatible with our observations and in line with the idea, that the majority of the Si iii absorbers at z ≤ 0.1 arise in the extended halos of low-redshift galaxies. For the future, we are planning to further explore the relation between intermediate-ion absorbers and galaxies at low z using higher-resolution simulations from the EAGLE (Evolution and Assembly of GaLaxies and their Environments) project (Schaye et al 2015).…”
Section: Comparison With Hydrodynamical Simulationssupporting
confidence: 89%
“…The line statistics from synthetic absorption spectra generated from such simulations can be directly compared to QSO absorption-line studies to investigate the different gas phases in the IGM and CGM and their redshift evolution (Fang & Bryan 2001;Richter et al 2006;Fangano et al 2007;Tepper-García et al 2011, 2012, 2013Oppenheimer et al 2012;Smith et al 2011;Churchill et al 2015).…”
Section: Comparison With Hydrodynamical Simulationsmentioning
confidence: 99%
“…These observations could be confronted with cosmological hydrodynamical simulations that included metal enrichment from galactic superwinds to learn how the nucleosynthetic products of star formation enrich the diffuse CGM and IGM (e.g. Aguirre et al 2001;Schaye et al 2003;Springel & Hernquist 2003b;Oppenheimer & Davé 2006Tornatore et al 2010;Wiersma et al 2010;Cen & Chisari 2011;Smith et al 2011;Tepper-Garcia et al 2011;Tescari et al 2011;Oppenheimer et al 2012;Crain et al 2013;Rahmati et al 2016).…”
mentioning
confidence: 99%
“…Alternatively, if O VI is primarily collisionally ionized at its 10 5.5 K peak (e.g. Heckman et al 2002;Cen & Chisari 2011;Smith et al 2011;Tepper-Garcia et al 2011;Faerman, Sternberg & McKee 2016), then it signals a hot halo component apparently associated with star-forming galaxies. Is this warm-hot component related to recent outflows or does it trace the temperature of a virialized, quasi-static halo?…”
mentioning
confidence: 99%
“…Numerical simulations (Cen & Ostriker 1999;Davé et al 1999, Cen & Ostriker 2006, Smith et al 2011 indicated that only 10-20% of all baryons are in collapsed objects. Baryons in Intergalactic Medium (IGM) exist in a wide range of densities and temperatures.…”
mentioning
confidence: 99%